2017
DOI: 10.1016/j.livsci.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder involvement and the management of animal genetic resources across the world

Abstract: The sustainability of activities related to animal genetic resources (AnGR) management depends largely on the participation of a range of stakeholders, both public and private. In this study, we investigated factors explaining differences in stakeholder involvement in AnGR management across countries, based on an historical perspective and an analysis of the 128 official country reports provided during preparation of The Second Report on the State of the World's Animal Genetic Resources for Food and Agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 24 publications
1
35
0
1
Order By: Relevance
“…Some countries in the region have well developed public and private institutions, which can be used for in situ conservation herds [51]. Leroy et al [52] recommended that the success of a breeding scheme should be compatible with the breeding objective of the farming system. It was further suggested that there should be greater collaboration with smallholder farmers complemented with market incentives and institutional support services [53].…”
Section: Cattle Breeding and Reproduction Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some countries in the region have well developed public and private institutions, which can be used for in situ conservation herds [51]. Leroy et al [52] recommended that the success of a breeding scheme should be compatible with the breeding objective of the farming system. It was further suggested that there should be greater collaboration with smallholder farmers complemented with market incentives and institutional support services [53].…”
Section: Cattle Breeding and Reproduction Strategiesmentioning
confidence: 99%
“…To effectively implement the suggested strategies for sustainable use of indigenous cattle breeds, partnerships and collaboration among stakeholders (Figure 1) in the preparation and implementation of a strategic long-term plan is essential. Stakeholder participation is important because cattle genetic resources are commonly managed as a common good involving private and public interests [52]. Stakeholder involvement includes participation in animal-, marketing-, and policy-level activities.…”
Section: Institutional Support Strategiesmentioning
confidence: 99%
“…Historical knowledge and individual productivity are fundamental for flock grouping [27], especially for feeding strategies [28,29] and genetic improvement programs [30], which consist of identifying and grouping animals with predetermined characteristics (mainly milk yield and prolificacy). Moreover, these programs require a considerable amount of human, animal and material resources [31,32]. The identification and grouping of animals for breeding purposes is often highly labor-intensive, commonly involving from two to three operators.…”
Section: Introductionmentioning
confidence: 99%
“…Ils soulignent notamment l'augmentation de la concurrence entre les acteurs qui coopéraient auparavant, la libéralisation des activités de sélection et, des changements dans la gouvernance des races animales. Une étude comparative récente à l'échelle internationale (Leroy et al, 2017) souligne la nécessité d'une coopération des acteurs publics et privés dans le management des ressources génétiques animales et met en avant l'importance de l'implication des éleveurs. Pourtant, ce sont ces mêmes dimensions qui se trouvent questionnées dans le contexte des changements technologique et règlementaire actuels.…”
unclassified